Analisis Penerapan Key Performance Indicators (KPI) dalam Upaya Meningkatkan Kecakapan Pegawai untuk Pengembangan Karir di PT ANTAM Tbk - Unit Geomin - Zahra, Luthfiah; Syamsurizal; Sofa , Nidia; Utomo , Wahyudi; Firdaus , Risya Zahrotul (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
This research aims to know and analyze the implementation of KPI, the effort to improve employee prowess, and career development at PT ANTAM Tbk – Unit Geomin. The research method used is qualitative research method. In this research, data collection techniques used interview, observation, and document. Data analysis techniques used Miles & Huberman with NVivo 12. The result indicates that implementation of KPI at PT ANTAM Tbk – Unit Geomin are held appropriate with applicable guidelines, but the result of KPI achievements for several employees in Department levels showed that it wasn’t optimal. The average of KPI achievements were down in different years that showed by unstable final point of SMUK. The majority of employees were stagnant at the ‘Good’ category even a decline from the ‘Very Good’ to ‘Good’ and from ‘Good’ to ‘Fair’. In an effort to improve employee prowess from KPI are held through technical or skills training, knowledge sharing, certification, seminars, webinars, conferences, and assessment based on SMUK scores. Career development from KPI held through Performance Improvement Planning (PIP) for education and training which uses SMUK scores for increasing competency to achieve KPI, promotion and job transfer programs which use SMUK scores for the selection requirements and one of the aspects that determine final selection ranking.